Rancang Bangun Alat Pemotong Kerupuk Terasi dengan Menggunakan Senar Gitar - Muhamad Zainudin; Jaelani Jaelani; Fitri Nur Fauziah (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
Crackers are a typical Indonesian food that is very popular with various groups because of its crunchy texture and distinctive savory taste. One type of cracker that is often found is shrimp paste crackers, which are made from flour with the addition of shrimp paste, spices, and raising agents. In the production process, sophisticated technology is needed to increase production efficiency so that it can save energy, time, and costs. However, production equipment produced by factories is often expensive and difficult for the public to reach. Therefore, appropriate technology has emerged that is designed to help the community, one of which is a manual cracker cutter. This tool is designed to speed up and simplify the process of cutting crackers with uniform cutting results, namely 2-5 mm thick. Based on the trial, the cracker cutter using guitar strings showed significant time efficiency compared to a kitchen knife. The total cutting time with a kitchen knife reached 6 minutes 88 seconds, while using a cutter only took 42 seconds, with a time difference of 6 minutes 18 seconds. These results show that a manual cracker cutter based on guitar strings can increase efficiency and productivity in the cracker production process.